Energy harvesting in tuned liquid column dampers using Savonius type hydrokinetic turbines. (1st March 2023) - Ding, Hao; Zhou, Tian-Yu; Wang, Jin-Ting; Altay, Okyay; Zhang, Jian
Abstract: In this study, a new method that combines the tuned liquid column damper (TLCD) and the Savonius type hydrokinetic turbine (STHT) is proposed to harvest energy from mechanical vibrations of structures in a green power production way. The proposed approach converts hydrokinetic energy into electrical energy during the vibration control process. Excessive shaking table tests are performed to investigate the starting performance and energy conversion efficiency. An optimized circuit configuration is revealed for power maximization. The impact of STHT on the dynamic characteristics of TLCD is elaborated. In addition, a parallel circuit that allows both charging of energy storage components and vibration control is illustrated and experimentally verified. The results demonstrate the feasibility and characteristics of the approach in energy harvesting. Graphical abstract: Highlights: A new method is developed for energy harvesting from structural vibration. A tuned liquid column damper is coupled with a Savonius type hydrokinetic turbine. The impact on the dynamic behavior of the damper is elaborated. The starting and energy conversion performances are experimentally studied. A charging circuit that allows both energy storage and vibration control is shown.